Functions of the Deed of Sale and Purchase in the Issuance of a Certificate of Title to Land - Indrati Rini (PT FORMOSA CENDEKIA GLOBAL, 2023)
Buying and selling land is one type of agreement that is often carried out by community members. The deed of land sale and purchase agreement, including the building / house located on it must be carried out by the parties in the presence of an authorized official, namely a Notary / Land Deed Making Officer. To ensure legal certainty of the transfer of property rights to land, it is stated in the form of an authentic deed, for the validity of ownership of the land, it is necessary to prove the existence of a title certificate. The validity of the land sale and purchase deed affects the issuance of a title certificate made by the National Land Agency. In practice, there are often cases related to land sale and purchase deeds as the basis for issuing a title certificate.